Ribavirin induces hepatitis C virus genome mutations in chronic hepatitis patients who failed to respond to prior daclatasvir plus asunaprevir therapy. Issue 2 (16th October 2019) - Saito, Yuhei; Imamura, Michio; Uchida, Takuro; Osawa, Mitsutaka; Teraoka, Yuji; Fujino, Hatsue; Nakahara, Takashi; Ono, Atsushi; Murakami, Eisuke; Kawaoka, Tomokazu; Miki, Daiki; Tsuge, Masataka; et al.
Abstract: Ribavirin (RBV) induces nucleotide (nt) substitutions in hepatitis C virus (HCV) genome nonstructural (NS) regions. Although emergence of drug resistance‐associated variants is associated with direct‐acting antiviral treatment failure, the effect of RBV on genome substitutions in such patients is unknown. Genotype 1b HCV subgenomic replicon cells were treated with RBV for 120 hours. Six patients with chronic genotype 1b with HCV‐infected patients who failed to respond to prior daclatasvir plus asunaprevir (DCV/ASV) therapy were treated with 12 weeks of sofosbuvir and ledipasvir plus RBV after 4 weeks of RBV monotherapy. RBV‐induced genome mutations in the HCV NS region (nt3493‐9301) in replicon cells and in patients during 4 weeks of RBV monotherapy were analyzed by deep sequencing. RBV‐associated G‐to‐A and C‐to‐U transitions increased in a dose‐dependent manner in HCV replicon cells after the RBV treatment. In patients with prior DCV/ASV treatment failures, the median serum HCV RNA level was 6.25 ± 0.31 log IU/mL at the start of RBV therapy and decreased significantly to 5.95 ± 0.4 log IU/mL ( P  = .03) after 4 weeks of RBV monotherapy. Although predominant HCV genome substitutions rates were similar between nontreatment and RBV‐treatment periods (0.042 and 0.031 per base pair, respectively; P   = .248), the frequencies of G‐to‐A and C‐to‐U transitions significantly increased after RBV monotherapy. These transitions were enriched, particularly within the HCV NS3 region in all patients. RBV treatment induces G‐to‐A and C‐to‐U transitions in the HCV genome even in chronic patients with hepatitis C with prior DCV/ASV treatment failures. Highlight: Ribavirin induces hepatitis C virus genome G‐to‐A and C‐to‐U transitions in patients with prior daclatasvir plus asunaprevir treatment failures. G‐to‐A and C‐to‐U transitions were enriched, particularly in hepatitis C virus NS3 region in patients with prior daclatasvir plus asunaprevir treatment failures.